The Gastrointestinal Parasites in Habituated Group of Sulawesi Black-crested Macaque (Macaca nigra) in Tangkoko, North Sulawesi - Sitti Aisyah May Wulandari; Dyah Perwitasari-Farajallah; Erni Sulistiawati (Journal of Tropical Biodiversity and Biotechnology, 2022)
The Sulawesi black-crested macaque (Macaca nigra) is an endemic primate of North Sulawesi that is categorized as critically endangered (IUCN 2015). Endoparasite contributes to the decline of M.nigra. Therefore, this study aims to determine the prevalence of endoparasites in the Sulawesi black-crested macaque (M. nigra). We collected 80 fresh fecal samples representing all sex from the two habituated groups. We analyzed them using the direct examination technique (0.9% NaCl, iodine, methylene blue) and flotation technique with the modified McMaster test. A total of 15 endoparasite taxa were recorded and 78 of 80 samples were infected with at least one or several endoparasite taxa. Around 93.75% (75/80) samples were positive for protozoa (Balantidium sp., Entamoeba sp., Giardia sp., and Isospora sp.) and 88.75% (71/80) samples were positive for helminths (Ancylostoma sp., Strongyloides sp., Haemonchus sp., Trichuris sp., Trichostrongylus sp., Ascarid sp., Diphyllobothrium sp., Echinococcus sp., Hymenolepis sp., Schistosoma japonicum and Schistosoma mekongi). The abundance of protozoa was higher than helminth, although the number of helminth taxon (11) was higher. The average temperature and monthly rainfall did not affect the number of endoparasites (EPG). The prevalence was higher in females than males due to different social styles; female crested macaques are more tolerant than males. The group with a larger number of individuals had a higher prevalence of endoparasites. These results confirm the presence and high diversity of gastrointestinal endoparasites in M. nigra, which can help to understand transmission dynamics and zoonotic potential, as well as to consider conservation policies.